Gut microbiome-mediated epigenetic modifications in gastric cancer: a comprehensive multiomics analysis - Qian, Zixing; Bai, Wei; Li, Jiaxuan; Rao, Xianjun; Huang, Guodong; Zhang, Xueping; Wu, Wenyu; Liu, Jiabao; Wei, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundGastric cancer (GC), a malignant and highly proliferative disease, has profoundly impacts a substantial global population and is associated with several variables, including genetic, epigenetic, and environmental impacts. Global variance is associated with Helicobacter pylori infection and dietary factors.ObjectivesThe aim of the present study was to understand and identify key genes significantly modulated by epigenetic changes that can serve as biomarkers and therapeutic targets for gastric cancer.MethodsThis study employed an integrative multiomics approach to investigate gut microbiome-mediated epigenetic modifications in gastric cancer by utilizing publicly available transcriptomic and DNA methylation datasets, Quality control, normalization and deferentially expressed gene analysis of sequencing data were performed via standard bioinformatics pipelines. Functional enrichment analyses, including GO and KEGG pathway mapping, were performed to elucidate the biological pathways influenced by these interactions and network analysis was conducted using Cytoscape to identify hub genes. We conducted in vitro assays using the gastric adenocarcinoma cell lines AGS and MKN45, and the normal gastric epithelial cell line GES-1. The expression of selected candidate genes was evaluated using real-time PCR in these cell lines.ResultsThe GEO2R and coexpression network analyses revealed that six genes MAPK1, NOXO1, CUL1, CDK1, CDK2, and CCNB1 were significantly altered by modified DNA methylation and mRNA expression in GC. Owing to their identification across all epigenetic, transcriptomic, and miRNA datasets, we have designated these genes as shared genes. The results showed that the relative gene expression levels of MKN45 and AGS cell lines were higher than those in the GES-1 cell line in the control., and the results were aligned with the in silico findings.ConclusionsCDK1, CDK2, NOXO1, CUL1, MAPK1, and CCNB1 play pivotal roles in GC carcinogenesis and hold promise as early diagnostic biomarkers and therapeutic targets for GC.